Semantic Features of Lexemes Expressing the Meaning of "Action" In the Uzbek Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the article, the issues of semantic expression of Uzbek verbs in the lexical, morphological, syntactic level and the use of units meaning style in speech as a methodological tool are discussed.